The digital influence in the university environment - South of Minas Gerais (Research, Society and Development, 2021)
With the popularization of the internet, university behavior has been modified by Information and Communication Technologies (ICTs). Social networks have served as a means of communication, besides contributing to the sharing of knowledge. The objective is to identify how technology acts in the student experience of university students, interfering both in their studies and in their interpersonal relationships. For this, an online form was applied through the Google Forms platform, answered by 148 students from a private university in southern Minas Gerais, in order to understand the sociodemographic profile and the use of social networks by the sample. It was found that digital technologies are already well disseminated in the academic environment, especially in times of social isolation resulting from the COVID-19 pandemic, contributing both for obtaining knowledge and entertainment, and for communication. Digital influence was considered beneficial in the university environment, as it contributed positively to studies, as well as contributing to information sharing and interpersonal relationships at a distance.